2023
DOI: 10.1186/s12916-022-02692-8
|View full text |Cite
|
Sign up to set email alerts
|

Results of the phase IIa study to evaluate the efficacy and safety of rezivertinib (BPI-7711) for the first-line treatment of locally advanced or metastatic/recurrent NSCLC patients with EGFR mutation from a phase I/IIa study

Abstract: Background Rezivertinib (BPI-7711) is a novel third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI). This phase IIa study was part of a phase I/IIa study (NCT03386955), aimed to evaluate the efficacy and safety of rezivertinib as the first-line treatment for patients with locally advanced or metastatic/recurrent EGFR mutated non-small cell lung cancer (NSCLC). Methods Patients received the first-line treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Rezivertinib selectively inhibits the proliferation of EGFR mutated cells in cell lines. 142,[169][170][171] Covalent EGFR inhibitors in clinical trials. Currently, several covalent EGFR inhibitors are undergoing clinical trials, all of which are third-generation or more advanced EGFR TKIs.…”
Section: Covalent Egfr Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rezivertinib selectively inhibits the proliferation of EGFR mutated cells in cell lines. 142,[169][170][171] Covalent EGFR inhibitors in clinical trials. Currently, several covalent EGFR inhibitors are undergoing clinical trials, all of which are third-generation or more advanced EGFR TKIs.…”
Section: Covalent Egfr Inhibitorsmentioning
confidence: 99%
“…427 In 2019, Macdonald et al discovered a class of Myc-WDR5 inhibitors with a sulfonamide structure via high-throughput screening (HTS). 428 Although compound (170) was the most active (IC 50 = 29 nM), it was unsuitable for in vivo studies. To address this, Chacon Simon et al identified several other compound fragments via NMR fragment screening, resulting in compound (171) (IC 50 = 100 nM).…”
Section: Myc Ppi Inhibitorsmentioning
confidence: 99%